2021
DOI: 10.1093/jhered/esab057
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Analysis of Effective Population Size and Mating System in a Social Wasp

Abstract: Highly social species are successful because they cooperate in obligately integrated societies. We examined temporal genetic variation in the eusocial wasp Vespula maculifrons in order to gain a greater understanding of evolution in highly social taxa. First, we wished to test if effective population sizes of eusocial species were relatively low due to the reproductive division of labor that characterizes eusocial taxa. We thus estimated the effective population size of V. maculifrons by examining temporal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…A reduction in N e increases the intensity of genetic drift [31], and consequently reduces the efficacy of both negative and positive selection [27,32]. Termites are expected to have a very low N e relative to their census population size due to the complex social structure of their colonies, the small number of reproductive individuals (typically one king and one queen per colony), and their history of inbreeding within colonies [11,33,34]. Indeed, Romiguier et al [5] found that the termite Reticulitermes grassei had a large reduction in N e , even compared with other eusocial species, and postulated that this was due to the strict monogamy seen in this taxon.…”
Section: Results and Discussion (A) Genome Assemblies And Orthologue ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in N e increases the intensity of genetic drift [31], and consequently reduces the efficacy of both negative and positive selection [27,32]. Termites are expected to have a very low N e relative to their census population size due to the complex social structure of their colonies, the small number of reproductive individuals (typically one king and one queen per colony), and their history of inbreeding within colonies [11,33,34]. Indeed, Romiguier et al [5] found that the termite Reticulitermes grassei had a large reduction in N e , even compared with other eusocial species, and postulated that this was due to the strict monogamy seen in this taxon.…”
Section: Results and Discussion (A) Genome Assemblies And Orthologue ...mentioning
confidence: 99%
“…The first hypothesis posits that the presence of very few reproductive individuals within colonies should result in eusocial insects having small effective population sizes (N e ). This would be expected to increase the strength of genetic drift in eusocial lineages, leading to higher evolutionary rates [3,5,[9][10][11][12] (but see [13]). The second hypothesis states that the specific expression of genes in different castes should reduce pleiotropy and distinct selection pressures acting on these genes (i.e., 'indirect selection'), leading to the reduced efficacy of selection [6,7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we examined genetic differences between perennial and annual colonies of V. squamosa using the program GDA (Lewis & Zaykin, 2000 ). Vespula species within their native ranges do not show significant variation in allele frequency and genetic diversity over time (Dyson et al, 2021 ). Thus, analysis of genetic differences between V. squamosa annual and perennial colonies in this study would provide a rudimentary test of genetic differentiation between social forms.…”
Section: Methodsmentioning
confidence: 99%
“…A reduction in N e increases the intensity of genetic drift [32], and consequently reduces the efficacy of both negative and positive selection [27,33]. Termites are expected to have a very low N e relative to their census population size due to the complex social structure of their colonies, the small number of reproductive individuals (typically one king and one queen per colony), and their history of inbreeding within colonies [11,34,35]. Indeed, Romiguier et al [3] found that the termite Reticulitermes grassei had a large reduction in N e , even compared with other eusocial species, and postulated that this was due to the strict monogamy seen in this taxon.…”
Section: (C) Relaxed Selection In Termite Genomes Is Better Explained...mentioning
confidence: 99%
“…This would be expected to increase the strength of genetic drift in eusocial lineages, leading to higher evolutionary rates (e.g. through weaker purifying selection) [3,5,[9][10][11][12] (but see [13]). The second hypothesis states that the specific expression of genes in different castes and the reduction of multi-caste pleiotropy should result in distinct selection pressures acting on these genes for the different castes (i.e.…”
Section: Introductionmentioning
confidence: 99%